PELITA RAKYAT: Peningkatan Kompetensi Guru dalam Penerapan Psychological First Aid (PFA) sebagai Penanganan Dini Masalah Psikososial Siswa Sekolah Rakyat - Rusdi Rusli; Risna Febriani; Siti Raiyati (Jurnal Pendidikan dan Pengabdian Masyarakat, 2026)
The partner in this community service activity is the Integrated People's School 9 Banjarbaru with 48 teachers and educational staff participating. This school is relatively new and has been operating for approximately eight months. The problems faced are the limited competence of teachers in recognizing early signs of students' psychosocial problems, a lack of understanding of Psychological First Aid (PFA), and teachers' uncertainty in providing initial psychological support to students experiencing emotional distress. The solution offered is the implementation of group-based training and psychoeducation on Psychological First Aid (PFA). The target outputs to be achieved are increasing teacher competence in identifying psychosocial problems, implementing empathetic communication, providing initial psychological support, and understanding the referral mechanism to professionals. The implementation method is carried out through initial discussions, interactive material delivery, case discussions, PFA implementation simulations, reflection sessions, and evaluation through pre-tests and post-tests. The results of the activity show a significant increase in participants' understanding and competence regarding the implementation of PFA in the school environment. This activity has proven effective in strengthening teachers' readiness to provide initial psychosocial support and supporting the creation of a more supportive and responsive school environment for students' mental health.